2001
DOI: 10.1088/0022-3727/34/12/325
|View full text |Cite
|
Sign up to set email alerts
|

Optical emission spectra of a copper plasma produced by a metal vapour vacuum arc plasma source

Abstract: Optical emission spectroscopy in the range from 200 to 800 nm was applied for investigation of the copper plasma produced by a metal vapor vacuum arc plasma source. The experiments were conducted for the cases when the plasma was guided by straight and Ω-shaped curved solenoids as well as without solenoids and, also, for different vacuum conditions. It was found that, besides singly and doubly charged ions, a relatively high concentration of excited neutral copper atoms was present in the plasma. The relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Regarding the less doped sample of this series, it shows both a peak at 2.9 eV which is usually related to surface effects or dislocations in ZnO[22,23] and the characteristic green emission of ZnO, about 2.36 eV usually attributed to defects such as oxygen vacancies[24], even if much weaker, the yellow-orange emission typically associated with the presence of Zn vacancies[25], it is also visible. For dopant concentrations above 3.3 at%, emissions associated with the Cu ions centred in the area between 580 and 700 nm are clearly visible[20].Spectra from samples in series B are shown in figure 6b-c. Significant changes respect to the cathodoluminescence emission from series A samples can be found.…”
mentioning
confidence: 96%
“…Regarding the less doped sample of this series, it shows both a peak at 2.9 eV which is usually related to surface effects or dislocations in ZnO[22,23] and the characteristic green emission of ZnO, about 2.36 eV usually attributed to defects such as oxygen vacancies[24], even if much weaker, the yellow-orange emission typically associated with the presence of Zn vacancies[25], it is also visible. For dopant concentrations above 3.3 at%, emissions associated with the Cu ions centred in the area between 580 and 700 nm are clearly visible[20].Spectra from samples in series B are shown in figure 6b-c. Significant changes respect to the cathodoluminescence emission from series A samples can be found.…”
mentioning
confidence: 96%
“…Similarly Zhu et al report thin dense lamellar YSZ coatings [14]. Many other authors have reported examples of PS-PVD coatings [1,6,7,[9][10][11][12][13][15][16][17].…”
Section: Coating Examples (Ps-pvd and Ps-tf)mentioning
confidence: 98%
“…Considerable vaporization of the powder also occurs at high power levels. This is evident in Figure 5, where 5 micron copper powder injected into a VLPPS plasma jet produces an intense green emission from multiple spectral lines of copper vapor in the 505-530 nm wavelength range [1]. Phase transformation pathways and how process inputs affect feedstock treatment are also not well understood, though visible emission upon feedstock injection clearly indicates that the vaporized feedstock can be excited in the plasma prior to deposition.…”
Section: Plasma Jet Properties At Very Low Chamber Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the diagnostics based on the thermal emission of solid or liquid particles, for example by the DPV-2000, are not applicable. Optical emission spectroscopy (OES) however can be used to determine the properties of the plasma jet [4][5][6][7][8] and was also introduced to characterize the injected material in thermal spray processes such as the VPS/LPPS [9].…”
Section: Introductionmentioning
confidence: 99%